2013
DOI: 10.1055/s-0032-1318197
|View full text |Cite
|
Sign up to set email alerts
|

A Mild and Highly Efficient Conversion of Arylboronic Acids into Phenols by Oxidation with MCPBA

Abstract: A mild and highly efficient synthesis of phenols from arylboronic acids in a H 2 O-EtOH (1:2) solution was achieved by using MCPBA as the oxidant at room temperature. Isotopical labeling studies had shown that the hydroxyl oxygen atom of the phenol might originate from the MCPBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Over the past few decades, various protocols have been established for transition metal-free oxidative hydroxylation of boron reagents. Most of these methods used stoichiometric, usually excessive amounts of unstable, strongly oxidative or even potentially explosive oxidants, such as hydrogen peroxide, 4 TBHP, 5 oxone, 6 amine oxide, 7 m -CPBA, 8 hypervalent iodine, 9 NaBO 3 , 10 and so on (Scheme 1a). This greatly limited their broad applications in organic synthesis.…”
mentioning
confidence: 99%
“…Over the past few decades, various protocols have been established for transition metal-free oxidative hydroxylation of boron reagents. Most of these methods used stoichiometric, usually excessive amounts of unstable, strongly oxidative or even potentially explosive oxidants, such as hydrogen peroxide, 4 TBHP, 5 oxone, 6 amine oxide, 7 m -CPBA, 8 hypervalent iodine, 9 NaBO 3 , 10 and so on (Scheme 1a). This greatly limited their broad applications in organic synthesis.…”
mentioning
confidence: 99%
“…Therefore, the synthesis of phenols and their derivatives has been widely studied . With the emergence of more and more efficient methods for the synthesis of arylboronic acids, oxidative hydroxylation of arylboronic acids to synthesize phenols is one of the most important transformations, which has attracted huge attention in the past decade. For example, the use of noble metals and/or stoichiometric amounts of strong oxidants (hydrogen peroxide, PhI­(OAc) 2 , mCPBA, benzoquinone, TBHP, oxone, amine oxide, and NaBO 3 ) effectuated the direct oxidative hydroxylation of arylboronic acids to access phenols and derivatives. In addition, an efficient electrosynthesis of phenols from arylboronic acids has also been developed …”
mentioning
confidence: 99%
“…34 Arylboronic acids can be hydroxylated by strong oxidizing agents such as oxone, hydrogen peroxide, or meta-chloroperoxybenzoic acid (MCPBA), which are usually used in stoichiometric amounts and carefully controlled to avoid over-oxidation. [35][36][37][38] In pursuit of environmentally friendly methods, Cu(II) and Pd(II) catalysts have been investigated for oxidative hydroxylation of arylboronic acids with molecular oxygen, albeit using a stoichiometric strong base (KOH or NaOH). [39][40][41] Scaiano et al reported the photocatalytic hydroxylation of boronic acids with methylene blue as photosensitizer with high efficiency.…”
mentioning
confidence: 99%